Emerging Challenges & Issues of Pulses in Commodity Futures Market - Sukhadeve, Varsha S.; Biyani, Yogesh Yugalkishore (Indian Journal of Marketing, 2012)
Futures market enabled the various segments of commodity trade to utilize a platform for hedging and price risk management. Future trading in agricultural goods, and especially in pulses has neither resulted in price discovery nor loss of volatility in food prices. We observe the steep increases in spot prices for pulses along with a granger causal link from future to spot prices for commodities on which future data was available. Moreover, with the opening of cross-border trade, commodity prices have also been guided by the upward movements in prices in international markets. For India, further opening of the future market in commodities and especially of pulses needs to be dispensed with and be treated with caution, in order not to let speculators have a wider playground. Futures trading has also helped improve the dissemination of knowledge pertaining to pulses industry and generated a channel for smooth flow of price and other fundamental information among various stakeholders. Future trading also opens doors to more speculative markets.